Evaluation of BTEX adsorption in industrial effluent through the percolation method using rice husk ash as adsorbent material - Camacho, Alini Luísa Diehl; Santos, Emanuele Caroline Araujo dos; Filho, Jorge Augusto Berwanger; Miranda, Luis Alcides Schiavo; Moraes, Carlos Alberto Mendes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The aromatic petroleum hydrocarbons (benzene, toluene, ethylbenzene and xylenes) are highly volatile and toxic to human health and the environment. Adsorption is a physical-chemical process widely used in effluent treatment in which a material called adsorbate has the capacity to retain components dispersed in an aqueous medium on its surface. Studies of waste recovery demonstrate potentialities and more noble uses than the final disposal. In this sense, the ashes generated from the combustion of rice husk can be used as a by-product with various applications; in the case of this work, as adsorbent material, due to its amorphism and its high surface area. This study aimed to evaluate the adsorption of the aromatic components of a petrochemical effluent (formation water) with the use of two types of rice husk ash generated from two different grate combustion processes in a filtration system under positive pressure. The ashes were segregated and characterized according to their physical, chemical, mineralogical, and microstructural properties. The adsorption procedure by percolation consisted of 1L of petrochemical effluent for 45 g of adsorbent material. The samples of raw effluent were analyzed by gas chromatography. The results proved that the percentage of removal of BTEX composts in the segregated ash I did not potentialize the effect of the adsorption, being higher in the raw ash, with values of 90.2; 94.9; 83.3 and 100 %, while in ash II the effect of the segregation influenced the adsorption process only for the benzene and toluene, with removal values that went from 55.08 to 69.14 % and 69.23 to 75 %, respectively, in both of the ashes studied. The results obtained were inferior to those recommended by the legislation. Thus, the different combustion temperatures of the husk influenced in the characteristics, adsorption capacity, and BTEX removal efficiency by the adsorbate. Therefore, the positive filtration system can be used as a final polishing step in the treatment of petrochemical effluents, replacing conventional systems that use activated carbon.